Mathematical analysis of certain road safety indicators in the Russian Federation - A. G. Shevtsova (Вестник СибАДИ, 2022)
Introduction. A large number of fatalities on the roads of the Russian Federation is a significant state problem; to reduce this indicator, various target programs are being developed at the national level. To assess the achievement of the established target programs, it is necessary to perform a mathematical analysis of certain road safety indicators, which makes it possible to establish the most accurate mathematical model describing certain interrelationships of the indicators under consideration for the subsequent forecast and assessment of the achievement of the established target indicators, which will allow assessing the effectiveness certain guidelines of state policy in the area under consideration.Methods and materials. In the research work, methods of statistical and mathematical analysis, models for determining the state of road safety at different levels - world, state and regional, depending on various parameters are used.Results. A mathematical model for assessing road safety indicators based on the analysis of transport and social risk parameters is proposed, their low relationship is determined and the possibility of using them as independent parameters for assessing the state of road safety at the national level is established.Conclusion. The absence of a close relationship between the indicator of social risk and motorization, measured in the number of cars per 1000 inhabitants (the value of the correlation coefficient is 0,422), was found, which allows one to judge the presence of other factors influencing the parameter under consideration.